2003
DOI: 10.1111/j.1365-2249.2004.02342.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of interleukin-10-mediated inhibition of NF-κB activity: a role for p50

Abstract: SUMMARYNuclear factor kappa B (NF-k B) is a transcription factor pivotal for the development of inflammation. A dysregulation of NF-k B has been shown to play an important role in many chronic inflammatory diseases including rheumatoid arthritis, inflammatory bowel disease and psoriasis. Although classical NFk B, a heterodimer composed of the p50 and p65 subunits, has been well studied, little is known about gene regulation by other hetero-and homodimeric forms of NF-k B. While p65 possesses a transactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
194
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(211 citation statements)
references
References 45 publications
12
194
2
3
Order By: Relevance
“…In addition, a previous study using human monocytes indicated that IL-10 induced NF-B1 p105/p50 expression and increased p50/ p50 homodimers in the nucleus, an important element in the anti-inflammatory action of IL-10, while not affecting p105 protein stability after TNF␣ stimulation (54). These data suggest that IL-10 does not participate pivotally in the anti-inflammatory effect of EP4-EPRAP signaling, although IL-10 does appear to contribute to the anti-inflammatory action of PGE 2 , particularly in the late stage of LPS challenge.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, a previous study using human monocytes indicated that IL-10 induced NF-B1 p105/p50 expression and increased p50/ p50 homodimers in the nucleus, an important element in the anti-inflammatory action of IL-10, while not affecting p105 protein stability after TNF␣ stimulation (54). These data suggest that IL-10 does not participate pivotally in the anti-inflammatory effect of EP4-EPRAP signaling, although IL-10 does appear to contribute to the anti-inflammatory action of PGE 2 , particularly in the late stage of LPS challenge.…”
Section: Discussionmentioning
confidence: 93%
“…31 An important feature of TNF-a is the capacity to induce apoptosis under certain conditions, 32 as for example when the nuclear factor-jB pathway is blocked. 33 IL-10 can inhibit nuclear factor-jB (NF-kB) by the induction of p50/p50 homodimerization and its nuclear translocation; 34 therefore in the presence of IL-10, TNF-a will induce cell apoptosis. When IL-10 is absent, TNF-a will not induce apoptosis, instead it will promote the expres- sion of genes encoding pro-inflammatory cytokines, increasing immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that, in wt culture system, p50-containing dimers may act as repressor of Jagged1 gene expression. A vast array of information is available in the literature (Zhong et al, 2002;Driessler et al, 2004;Grundström et al, 2004) describing the specific role of p50 homodimers as transcriptional repressors within the family.…”
Section: Discussionmentioning
confidence: 99%